2016
DOI: 10.1002/anie.201511657
|View full text |Cite
|
Sign up to set email alerts
|

Facile Recoding of Selenocysteine in Nature

Abstract: Selenocysteine (Sec or U) is encoded by UGA, a stop codon reassigned by a Sec-specific elongation factor and a distinctive RNA structure. To discover possible code variations in extant organisms we analyzed 6.4 trillion base pairs of metagenomic sequences and 24,903 microbial genomes for tRNASec species. As expected, UGA is the predominant Sec codon in use. We also found tRNASec species that recognize the stop codons UAG and UAA, and ten sense codons. Selenoprotein synthesis programmed by UAG in Geodermatophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 34 publications
(51 reference statements)
1
65
0
1
Order By: Relevance
“…6B). Additional codon-anticodon variations have been reported, but have not yet been analyzed at depth regarding yields and efficiencies in final products of recombinant selenoproteins (29,49). Importantly, here we found that if UAG-directed TrxR1 production is performed in the RF1-depleted C321.⌬A host strain with a maintained variant SECIS element, almost full Sec content is achieved due to the fact that termination no longer occurs (Fig.…”
Section: Summary Of Yield and Specificity In Sec Insertion-mentioning
confidence: 52%
“…6B). Additional codon-anticodon variations have been reported, but have not yet been analyzed at depth regarding yields and efficiencies in final products of recombinant selenoproteins (29,49). Importantly, here we found that if UAG-directed TrxR1 production is performed in the RF1-depleted C321.⌬A host strain with a maintained variant SECIS element, almost full Sec content is achieved due to the fact that termination no longer occurs (Fig.…”
Section: Summary Of Yield and Specificity In Sec Insertion-mentioning
confidence: 52%
“…Given the vast amount of new genomic and metagenomic DNA sequence information generated in the past few years, we document here the current knowledge of natural deviations from the standard genetic code (45, 61, 79, 92, 94, 98, 115, 125, 134, 157) (Figure 2) (Supplemental Figure 1). Previously, it was well known that Candida yeast reassigns the CUG codon from leucine (Leu) to serine (Ser) (60) and that many ciliates reassign either the UGA stop codon or both the UAA and the UAG stop codons to a canonical amino acid (12, 61, 88, 119) (Figure 2).…”
Section: Natural Expansion Of the Genetic Codementioning
confidence: 99%
“…Selenocysteine, Sec, specification illustrates both aspects. It is specified by UGU in Aeromonas salmonicida , UAG in Blastococcus and UGA in Escherichia coli and eukaryotes [1]. In the great majority of vertebrate mRNAs, UGA specifies termination and how its meaning is dynamically redefined to specify selenocysteine in a very small number of coding sequences, 25 in humans, is of great interest.…”
Section: Introductionmentioning
confidence: 99%